The politics of exile in Renaissance Italy - Shaw, Christine (Italian Renaissance historian) (Cambridge studies in Italian history and culture., 2000)
This book provides the first systematic analysis of the role of exiles in the political life of fifteenth-century Italy. It also provides fresh perspectives on the nature and power of governments during this period, and on ideas about the legitimacy of political authority and political action.